Cheiro-oral-pedal syndrome of the pons and the role of imaging in diagnosis and management - Zachary I. Merhavy; Garrett D. Barfoot; Leah Dajani; Zainab Elmahmoud; Emmanuel Flores; Thomas C. Varkey (Open Exploration Publishing Inc., 2023)
The patient is a 58-year-old male who presented with chief complaints of right-sided numbness, tingling, and loss of temperature sensation in the upper and lower extremities. The patient's symptoms began around the face and right corner of the mouth [maxillary/mandibular (V2/V3) distribution] before descending to the arm, trunk, and followed by the lower leg and foot. His home medication regimen included lisinopril, atorvastatin, long and short-acting insulin, and amlodipine. During the interview, the patient admitted to abstinence from his medications. Upon examination, the patient was found to have a loss of hot and cold touch on the right side and expressed 2+ reflexes (brisk response; normal) on both upper and lower extremities. In the initial work-up of the patient, he received a computed tomography (CT) scan which demonstrated an area of potential ischemic infarct of one of the left sided pontine perforator arteries. Immediately at that time he was given a loading dose of 325 mg aspirin and started on 81 mg daily. Because of the patient's symptoms and risk factors, he was hospitalized for further additional work-up and eventually discharged on dual antiplatelet therapy. This case is intriguing as both neuroradiological reading and neurological examination helped with localization of the lesion and changing the treatment strategy of the patient. With a pontine perforator ischemic event, the harms of treatment with thrombolytics would have outweighed the benefits. This interprofessional work between neuroradiology, internal medicine, and neurology ensured that the patient received the best care for his specific ailments.